Neilonella sp. - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Neilonella sp. Fig. 7C, D. Material .— Five specimens (including two figured: ZPAL V.48/12, 13), partial shells, from the upper Paleocene of Fossildalen, Spitsbergen, Svalbard. Measurements .—L, 4.5–6.9 mm; H, 3.5–4.9 mm; W, 2.1– 3.0 mm; H/L, 0.71–0.80; W/L, 0.44–0.58; n = 5. Description. —Shell small, moderately inflated, elongate-ovate, equivalve, nearly equilateral. Surface sculptured with fine commarginal ribs. Antero-dorsal margin broadly rounded, passing into semicircular anterior margin; posterodorsal margin nearly straight, sloping gently into bluntly pointed posterior end; ventral margin broadly arcuate. Escutcheon not demarcated but broad. Beak not very prominent, slightly opisthogyrate, located centrally. Hinge with two series of very small teeth. Pallial sinus narrow, shallow, posterior muscle scar subquadrate. Remarks. —Although we could not determine the presence of a resilifer, the available specimens are considered to belong in Neilonella because of their elongate-ovate outline, the presence of many fine commarginal ribs on the shell surface and the bluntly pointed posterior end. They resemble Neilonella alleni Amano and Jenkins, 2017, from the Selandian (middle Paleocene) Katsuhira Formation in eastern Hokkaido, Japan, in their small size and in having sculpture of fine commarginal ribs. However, the anteriorly situated and more bluntly pointed beak of N. alleni enables us to separate it from the present species. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 110, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900